2004
DOI: 10.1159/000081881
|View full text |Cite
|
Sign up to set email alerts
|

Nonhabitual Seizures in Patients with Implanted Subdural Electrodes

Abstract: The implantation of subdural electrodes has been widely employed in the invasive monitoring of patients with medically refractory epilepsy. The use of subdural electrodes, though, has been associated with rare but occasionally troublesome complications. We report the occurrence of nonhabitual seizures after implanting subdural grid electrodes. Among 57 patients diagnosed with medically refractory epilepsy who were evaluated in our department over a 12-month period, 21 patients underwent craniotomy for subdural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Our finding has been previously reported in a smaller clinical series and explanations as to the possible pathophysiologic mechanisms implicated in the pathogenesis of this finding have been explored [3] . Malow et al [34] have reported a case of recording nonhabitual seizures in a patient with a SDH caused by a subdural grid implantation.…”
Section: Discussionsupporting
confidence: 79%
“…Our finding has been previously reported in a smaller clinical series and explanations as to the possible pathophysiologic mechanisms implicated in the pathogenesis of this finding have been explored [3] . Malow et al [34] have reported a case of recording nonhabitual seizures in a patient with a SDH caused by a subdural grid implantation.…”
Section: Discussionsupporting
confidence: 79%
“…Acute implantation can induce interictal epileptiform activity and seizures that do not accurately represent a patient’s underlying disorder 43,44 . This may be a result of direct effects, such as of trauma, electrode contact with the cortical tissue, or complications of electrode placement such as hemorrhage, fluid collections or cerebral edema 44 .…”
Section: Discussionmentioning
confidence: 99%
“…If present before resection, these symptoms are transient. New seizure patterns can develop due to cortical compression or contusion and if not properly identified lead to mis-localization of the epileptogenic focus; this may be related to subdural hematoma under the plates [42,43].…”
Section: Complicationsmentioning
confidence: 99%